2020
DOI: 10.1038/s41598-020-76818-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of red mud and waste glass on the microstructure, strength, and leaching behavior of bottom ash-based geopolymer composites

Abstract: The influence of waste glass and red mud addition as alternative source of aluminosilicate precursors on the microstructural, mechanical, and leaching properties of bottom ash-based geopolymer was studied in this work through mineralogical, morphological, and spectroscopic analysis, as well as by conducting compressive strength and leaching tests. The bottom ash-based geopolymer composites were synthesized by adding a constant amount of waste glass (10% by weight) and increasing amounts of red mud (up to 30% b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…On the other hand, the average values of the compressive strength increase as the SiO 2 /Al 2 O 3 molar ratio becomes higher. The result is consistent with Bobirica et al 49 . and Duxson et al., 7 who reported that the higher available reactive Si content largely increases the mechanical strength.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the average values of the compressive strength increase as the SiO 2 /Al 2 O 3 molar ratio becomes higher. The result is consistent with Bobirica et al 49 . and Duxson et al., 7 who reported that the higher available reactive Si content largely increases the mechanical strength.…”
Section: Resultssupporting
confidence: 91%
“…48 On the other hand, the average values of the compressive strength increase as the SiO 2 /Al 2 O 3 molar ratio becomes higher. The result is consistent with Bobirica et al 49 and Duxson et al, 7 who reported that the higher available reactive Si content largely increases the mechanical strength. The mixtures with SiO 2 /Al 2 O 3 theoretical molar ratio equal to 6 presented the best compressive strengths, indicating that the greater availability of silica may have contributed to the greater degree of geopolymerization.…”
Section: Mechanical Testssupporting
confidence: 91%
“…Combined with the previous research results [ 29 , 30 ], we observed a sharp peak at 450 cm −1 for Si–O–Si and O–Si–O bending vibrations and a peak at 715 cm −1 attributed to the CPB sample Si–O–T (symmetric stretching vibrations in middle aluminosilicate composites). The C–O bending vibration at 870 cm −1 and the C–O asymmetric stretching vibration at 1470 cm −1 were observed to be the peak characteristics in calcite.…”
Section: Resultssupporting
confidence: 89%
“…The degree of polymerization of the two gels presented different trends. Because the bond energy of Al–O is lower than that of Si–O [ 30 ], Al entered the amorphous material and participated in polymerization at the beginning of the reaction. Thus, the degree of aggregation was the highest at an age of 1 day.…”
Section: Resultsmentioning
confidence: 99%
“…Geopolymer materials have an advantage over the Portland cement-based binders which cause the emission of very large amounts of carbon dioxide. Fly ash, waste glass and slag were used as raw materials for the geopolymer which can decrease the carbon emission from these binder materials [3][4][5][6]. Metakaolin-based geopolymers are supposed as ''model-system" without the drawbacks inserted by using fly ash, slag, and other alternative starting materials which include several difficult-to-characterize amorphous phases [7].…”
Section: Introductionmentioning
confidence: 99%